CLUSTER ANALYSIS OF THE REGIONAL DEVELOPMENT OF THE TOURISM AND HOSPITALITY SECTOR OF UKRAINE - Savytskyi, Artem (Current Problems of Sustainable Development, 2026)
The article presents a cluster analysis of the regional development of the tourism and hospitality sector of Ukraine based on multidimensional methods. The study is aimed at identifying the spatial features of the functioning of regional tourism and hospitality systems, determining models of their development, and assessing the level of structural asymmetry under current socio-economic transformations. The information base of the study was formed using data from the State Statistics Service of Ukraine for 2018, 2021, and 2023, which made it possible to trace the dynamics of changes during the pre-crisis period, the pandemic  restrictions period, and under wartime risks. The study applies principal component analysis (PCA), the k-means clustering method, and self-organizing maps (SOM), which made it possible to reduce data dimensionality, cluster regions, and identify hidden spatial patterns in the development of the tourism and hospitality sector. It was determined that the first principal component reflects the scale and resource potential of the regions, while the second characterizes labor resource efficiency and operational performance of the sector. The results reveal an increase in spatial polarization and regional specialization of the tourism and hospitality sector of Ukraine. Four types of regional clusters were identified, differing in the scale of activity, level of resource provision, productivity, and institutional resilience. It is substantiated that the current structure of the tourism and hospitality sector is characterized by the dominance of a limited group of high-resource regions and a significant share of low-intensity territories with insufficient infrastructure and business activity. The obtained results confirm the feasibility of applying multidimensional methods to identify hidden patterns of spatial development and assess structural transformations in the tourism and hospitality sector of Ukraine. The practical significance of the study lies in the possibility of using the proposed approach for the formation of differentiated regional development policies, substantiation of managerial decisions, and determination of regional support priorities under structural economic transformations.
Keywords: tourism and hospitality sector; regional development; cluster analysis; multidimensional analysis; PCA; self-organizing maps; spatial analysis; regional clusters; modeling